Trp64Arg polymorphism of the ADRB3 gene associated with maximal fat oxidation and LDL-C levels in non-obese adolescents, - Jesus,Íncare Correa de (2018)
Abstract Objective: To analyze the association between the Trp64Arg polymorphism of the ADRB3 gene, maximal fat oxidation rates and the lipid profile levels in non-obese adolescents. Methods: 72 schoolchildren, of both genders, aged between 11 and 17 years, participated in the study. The anthropometric and body composition variables, in addition to total cholesterol, HDL-c, LDL-c, triglycerides, insulin, and basal glycemia, were evaluated. The sample was divided into two groups according to the presence or absence of the polymorphism: non-carriers of the Arg64 allele, i.e., homozygous (Trp64Trp: n = 54), and carriers of the Arg64 allele (Trp64Arg + Arg64Arg: n = 18), in which the frequency of the Arg64 allele was 15.2%. The maximal oxygen uptake and peak of oxygen uptake during exercise were obtained through the symptom-limited, submaximal treadmill test. Maximal fat oxidation was determined according to the ventilatory ratio proposed in Lusk's table. Results: Adolescents carrying the less frequent allele (Trp64Arg and Arg64Arg) had higher LDL-c levels (p = 0.031) and lower maximal fat oxidation rates (p = 0.038) when compared with non-carriers (Trp64Trp). Conclusions: Although the physiological processes related to lipolysis and lipid metabolism are complex, the presence of the Arg 64 allele was associated with lower rates of FATMAX during aerobic exercise, as well as with higher levels of LDL-c in adolescents.